2021
DOI: 10.37796/2211-8039.1123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on quality of sleep in patients with sleep disturbance admitted to post coronary care units: a randomized controlled trial

Abstract: The effect of melatonin on quality of sleep in patients with sleep The effect of melatonin on quality of sleep in patients with sleep disturbance admitted to post coronary care units: a randomized disturbance admitted to post coronary care units: a randomized controlled trial controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…According to the perception of participants, the uncertainty of the disease can cause psychosocial distress in patients' families. In this regard, the model of intolerance of uncertainty and ambiguity, which is considered as a new perspective in explaining anxiety, states that anxious people often perceive vague and indefinite situations as disturbing and stressful ( 22 ). As a result, they suffer from psychosocial distress in the face of such circumstances ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the perception of participants, the uncertainty of the disease can cause psychosocial distress in patients' families. In this regard, the model of intolerance of uncertainty and ambiguity, which is considered as a new perspective in explaining anxiety, states that anxious people often perceive vague and indefinite situations as disturbing and stressful ( 22 ). As a result, they suffer from psychosocial distress in the face of such circumstances ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status was classified based on occupation, income and educational status of patients ( 17 ). Socioeconomic status determined by combining the patients' occupational status [scores 1 to 3], education level [scores1 to 3] and place of residence [scores 1 to 2] and rated as low ( 3 ), middle ( 4 6 ) and high ( 7 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…[8] Providing palliative care has positive consequences such as an increase in the patient's energy, pain relief, dealing with the disease taboo, changing the lifestyle [9] and promoting the patient knowledge and awareness. [10] However, it can be impaired by challenging factors, including inefficient performance, poor or nonquality care or care that does not meet the standards, [11] progression of the destructive power of disease, [12] progressive dysfunction of daily function, [13] heterogeneous coverage and improper level of services [14] and inadequate access to care services. [15] Meier (2011) showed that chronic patients hospitalised in different wards do not receive optimal-quality palliative care services.…”
Section: Indian Journal Of Palliative Carementioning
confidence: 99%